2016
DOI: 10.1002/jso.24269
|View full text |Cite
|
Sign up to set email alerts
|

90Y radiation lobectomy: Outcomes following surgical resection in patients with hepatic tumors and small future liver remnant volumes

Abstract: In this preliminary study, radiation lobectomy was a safe and effective method to achieve remnant liver hypertrophy while providing tumor control. This approach may facilitate safe resection and favorable post-operative outcomes.J. Surg. Oncol. 2016;114:99-105. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…Limited therapy after progression permits the attribution of survival outcome solely to RS without confounders. Finally, the time to progression of 2.4 years (29 months) is comparable to the Prospective Randomized Trial of Radioembolization and Chemoembolization in HCC (or PREMIERE) trial, where greater than 26 months of time to progression was validated in a randomized setting (32). Also, the mean follow-up that are Child-Pugh class A BCLC stage 0 or A was evaluated.…”
Section: Vascular and Interventional Radiology: Radiation Segmentectomentioning
confidence: 93%
“…Limited therapy after progression permits the attribution of survival outcome solely to RS without confounders. Finally, the time to progression of 2.4 years (29 months) is comparable to the Prospective Randomized Trial of Radioembolization and Chemoembolization in HCC (or PREMIERE) trial, where greater than 26 months of time to progression was validated in a randomized setting (32). Also, the mean follow-up that are Child-Pugh class A BCLC stage 0 or A was evaluated.…”
Section: Vascular and Interventional Radiology: Radiation Segmentectomentioning
confidence: 93%
“…Neoadjuvant RL offers a unique advantage by delivering ablative transarterial brachytherapy in addition to generating FLR hypertrophy. The majority of patients in this series received RL doses greater than 200 Gy, higher than prior reported doses of 120-150 Gy in prior studies (23)(24)(25). Higher hepatic doses and concurrent systemic therapy were well-tolerated in these first line patients without significant clinical toxicity (grade I C-D complications) or hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 71%
“…Two out of four patients progressed after resection at 3 months and may have benefited from longer surveillance. Unlike PVE, patients in this study had a minimal time to resection of 3 months (25). This increased observational period may circumvent an unnecessary resection should there be FLR disease progression that cannot be addressed (7,26).…”
Section: A B a Bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to consider the feasibility and safety of surgery after SIRT, and to determine the impact of concomitant chemotherapy. A preliminary study of 13 patients who underwent SIRT followed by lobectomy found the approach to be an effective method to induce hypertrophy of the future liver remnant (FLR) prior to resection (89). The median time to resection in this study was 86 days (30-210 days); and with PVE the median time to resection was 37 days (21-84 days) (90).…”
Section: Sirt and Surgerymentioning
confidence: 71%